Identifying the paths leading to variation in geographical range size in western North American monkeyflowers. (15th July 2014) - Sheth, Seema N.; Jiménez, Iván; Angert, Amy L.; McGeoch, Melodie
Abstract Aim Closely related species can vary tremendously in size of geographical range, yet the causes of such variation are poorly understood. Prominent hypotheses about range size emphasize effects of niche properties and habitat connectivity via the amount and occupancy of suitable habitat, respectively. Previous studies have examined single hypotheses in isolation; however, we assessed the relative importance of these effects along with their potential interactions, using monkeyflower species (genus Mimulus) as a study system. Location Western North America. Methods We used primary occurrence data and climatic layers to estimate climatic niche breadth and position (relative to average regional climate), connectivity of climatically suitable habitat, and geographical range size of 72 monkeyflower species. Using path analysis, we then assessed the relative importance of climatic niche properties and connectivity of climatically suitable habitat in explaining variation in the amount and occupancy of climatically suitable habitat, respectively, and in turn, variation in geographical range size. Results We documented strong support for the hypothesized effects of climatic niche breadth, but not niche position and connectivity of climatically suitable habitat. Amount of climatically suitable habitat explained more variation in range size than occupancy of climatically suitable habitat, with amount and occupancy of suitable habitat together explaining c. 83% of the variation in range size. Main conclusions To our knowledge, this is the first study to show that climatic niche breadth, via its effects on the amount of climatically suitable habitat, is a strong predictor of geographical range size, thereby improving our understanding of the mechanisms driving species rarity.